The correlation of expression of VEGF and EGFR with SUV of 18FDG-PET-CT in non-small cell lung cancer - Liu, Xiguang; Zhang, Hongjun; Yu, Xiaoyun; Song, Tingting; Huang, Peng; Wang, Haichao; Song, Shan-ai (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study : To explore the correlation of the expression of vascular endothelial growth factor (VEGF) and epidermal growth factor receptor (EGFR) with maximum standardised uptake value (SUV max ) of 18 FDG-PET-CT in non-small cell lung cancer (NSCLC). Material and methods : Thirty patients received PET-CT imaging protocol first, and then all the patients underwent needle biopsy though CT guidance. The tumour tissue of each patient was taken from two biopsy areas: one area was SUV max = 2.5–5, and the other was SUV max > 5. Expression of VEGF and EGFR were detected and analysed by immunohistochemical staining. Results: The expressions of both VEGF and EGFR had no statistically significant correlation with SUV max in age, gender, pathology, or differentiation (p > 0.05). The expressions of both VEGF and EGFR had statistically significant correllation with SUV max in tumour size and clinical stage (p < 0.05). SUV max correlated positively with VEGF and EGFR expressions (r = 0.879, p < 0.05). Conclusions : SUV max correlated positively with expressions of VEGF and EGFR (r = 0.879, p = 0.000; r = 0.839, and p = 0.000, respectively). This study may provide guidance for radiotherapy of NSCLC.